Requirements of a New Substation based Protective Relay Coordination - Mehrdad Babazadeh; Vahid Farrokhi; Mojtaba Pour Eskandari (International Journal of Applied Methods in Electronics and Computers, 2016)
This paper brings together experiences of three years effort toward implementing an Overcurrent and Earth fault relay coordination software. A substation based coordination method has been developed by using the programing language, Vb.net and connection to the database, Microsoft Access. By this, sufficiency of the new proposed view is evaluated. Since short circuit calculation programs are usually available, a substation including all the current protective relays plus distance relays is considered in this applied research. A special attention is paid to define a few relevant short circuit scenarios and different rules are developed based on this methodology to achieve optimal settings and to cover instructions and standards. The resulted software program facilitates all the calculations of current relays for any high voltage substation with any configuration and offers detailed calculations. The results have been tested frequently on a large power system grid in a regional electric company for about 10 years.